2021
DOI: 10.1093/forsci/fxab022
|View full text |Cite
|
Sign up to set email alerts
|

Delayed Tree Mortality After Prescribed Fires in Mixed Oak Forests in Northwestern Ohio

Abstract: Delayed tree mortality can contribute to variability in fire effects in forests, but its prevalence is not well understood in eastern North American oak forests where a management goal is using prescribed fire to shape forest density and composition. To assess potential delayed mortality after prescribed fires, we tracked the fates of 690 trees of four species in burned and 542 trees in unburned oak forests in northwestern Ohio, USA, and modeled survival using tree diameter and bole char. Delayed mortality, oc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 33 publications
1
3
0
Order By: Relevance
“…These results suggest 3 further management applications or questions. First, while results revealed that browse damage to oak seedlings declined after deer culling, the seedlings are not transitioning to larger size classes (Abella et al 2021), consistent with widespread findings in eastern North American oak forests (e.g., Thomas‐Van Gundy et al 2014). Advancing oak seedlings to saplings often requires a combination of canopy gaps, fires, and low levels of deer herbivory (Nuttle et al 2013, Walters et al 2020).…”
Section: Management Implicationssupporting
confidence: 74%
“…These results suggest 3 further management applications or questions. First, while results revealed that browse damage to oak seedlings declined after deer culling, the seedlings are not transitioning to larger size classes (Abella et al 2021), consistent with widespread findings in eastern North American oak forests (e.g., Thomas‐Van Gundy et al 2014). Advancing oak seedlings to saplings often requires a combination of canopy gaps, fires, and low levels of deer herbivory (Nuttle et al 2013, Walters et al 2020).…”
Section: Management Implicationssupporting
confidence: 74%
“…The threshold for tree density was below 100–200 trees/ha. Trees generally remained above these thresholds for the first 23 y of the study, as prescribed fires had minimal influence on survival of large oaks, consistent with their resistance to low-severity fires (Abella et al 2021). It was after 2010, after wind damage halved overstory tree basal area and density, when some of the highest savanna plant cover and richness values appeared.…”
Section: Discussionmentioning
confidence: 71%
“…As tree canopy cover is also often used to characterize midwestern oak savannas, we developed regression equations with tree canopy cover data we collected some years to estimate canopy cover from tree density and basal area to enable converting among these measures (Supplemental Appendix S1). We selected <10 cm as a cutoff for saplings because these smaller stems are more readily top killed (although root systems can survive) by typical low-severity fires (Abella et al 2021) and to represent the dense sapling layer below overstory trees that can form on savanna sites during fire-free periods (Taft 2009; Figure 2). We based the number of fires in the last 3 y on calendar years preceding a sampling year, but excluding any fires in autumn the calendar year of sampling as autumn fires would be after summer sampling that calendar year.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation